Effect of Compression Rotation Intervals on Cardiopulmonary Resuscitation Quality: A Systematic Review and Meta-Analysis - Sawee, Chinnawudh; Churuangsuk, Chaitong; Vattanavanit, Veerapong (Archives of Academic Emergency Medicine, 2025)
Introduction: Reducing the compression rotation interval from 2 to 1 minute is expected to improve cardiopulmonary resuscitation (CPR) quality. This meta-analysis aimed to assess the effect of altering the compression rotation interval on key CPR quality parameters, including compression depth, rate, and rescuer fatigue. Methods: We systematically searched MEDLINE, EMBASE, Scopus, Google Scholar, Web of Science, and the Cochrane Controlled Register of Trials from their inception to May 15, 2025. We searched for randomized controlled trials, simulation studies, and crossover studies that compared 1-min and 2-min compression rotation times. The assessed outcomes included compression depth, rate, correctness, and rescuer fatigue, which were reported as the standard mean difference (SMD) with a 95% confidence interval (95% CI). Results: One randomized controlled trial and seven randomized crossover studies, involving 668 rescuers in total, using manikins, were included. The 1-min rotation group exhibited significantly greater compression depth, with an increase of 2.06 mm (SMD = 2.06, 95% CI: 0.44–3.68, p < 0.001). This group demonstrated lower levels of fatigue, as indicated by a significant reduction on the visual analog scale for fatigue (SMD = −1.27, 95% CI: −2.24 to −0.30, p < 0.001). However, there were no significant differences in the compression rate or percentage of compressions that achieved adequate depth. Conclusion: It seems that altering the chest compression rotation interval from 2 min to 1 min improves the compression depth and reduces rescuer fatigue. However, parameters, such as the compression rate and compression adequacy, remained unchanged. Notably, all the studies were conducted on manikins, thus necessitating further research to assess the applicability of these changes in real-world clinical settings.